Prevalence and Risk Factor Assessment of Gastrointestinal Parasitic Infections in Cattle of Flood Prone Eastern Plains of Rajasthan - Saini, Priyanka; Gupta, Abhishek; Rathore, Bhavana; Meena, Abhishek Kumar; Kumari, Kavita; Saini, Pawan; Saini, Priya (International Journal of Bio-resource and Stress Management, 2024)
A total of 756 faecal samples (429 from native cattle and 327 from crossbred cattle) from flood prone eastern plains of Rajasthan were examined from January, 2022 to December, 2022. Out of them, 527 samples were found positive, with an overall prevalence of 69.71% for different gastrointestinal parasitic infections with mixed infection in 26.85%. The study revealed strongyles (43.25%) and Eimeria sp. (30.29%) as the most dominant infections followed by, Strongyloides sp., Amphistomes, Trichuris sp., Moniezia sp., B. coli and Capillaria sp.. Season wise analysis revealed a highly significant statistical seasonal variation (p<0.01) with maximum infection in rainy season (77.95%) whereas, a non-significant statistical difference in district wise prevalence was reported with the highest prevalence rate in Bharatpur district (76.47%). Quantitative analysis based on the estimation of oocysts and eggs gram-1 (OPG and EPG) of faeces revealed highest severity of Eimeria sp. infection ranging from 300–2200 (1107.14±171.12) followed by strongyle infection 200–1200 (509.09±84.70). Coproculture examination exhibited Haemonchus sp. as a predominant nematode genus, followed by Oesophagostomum sp., Bunostomum sp., Trichostrongylus sp., Cooperia sp., Chabertia sp., Ostertagia sp. and Strongyloides sp.. Sporulation studies showed higher prevalence of Eimeria bovis followed by E. zuernii, E. subspherica, E. auburnensis, E. ellipsoidalis, E. cylindrica, E. pellita, E. alabamensis, E. bukidnonensis and E. canadensis. The findings of the present study may be used to formulate effective control strategies against gastrointestinal parasitic infections in the cattle of the region.